2011
DOI: 10.1111/j.1099-0860.2010.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Being the Older Sibling: Self‐Perceptions of Children with Disabilities

Abstract: This exploratory study explored the experience of being an older sibling, from the perspective of children with disabilities. A phenomenological approach was used to investigate the experiences of 10 children with disabilities. The participants described engagement in older sibling roles that they perceived to positively influence their sense of self. In most instances participants perceived family dynamics, gender and personality to be more influential on this engagement than their impairment. Children with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…A large variety of participatory tools were used such that children could choose different activities (Kelly, 2007) and shape their interactions with the interviewers according to their own interests (Serendity & Burgman, 2012). One main strength of participatory techniques is their ability to foster communication (Christensen & James, 2008), and the findings show that the children were happy when they were able to recognize the pictures and used the tools in unique ways to express their perspectives.…”
Section: Participatory Tools: Multimodal Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A large variety of participatory tools were used such that children could choose different activities (Kelly, 2007) and shape their interactions with the interviewers according to their own interests (Serendity & Burgman, 2012). One main strength of participatory techniques is their ability to foster communication (Christensen & James, 2008), and the findings show that the children were happy when they were able to recognize the pictures and used the tools in unique ways to express their perspectives.…”
Section: Participatory Tools: Multimodal Communicationmentioning
confidence: 99%
“…Previous research has consistently shown that children with disabilities are capable of constructing and expressing their own views on different topics, such as their competence (Kramer & Hammel, 2011), their understanding of disability (Connors & Stalker, 2007;Merrick & Roulstone, 2011), friendship experiences (Morrison & Burgman, 2009), literacy experiences (Flewitt, Nind, & Payler, 2009), being the older sibling (Serendity & Burgman, 2012), their experiences with school (Ajodhia-Andrews & Berman, 2009;De Schauwer, Van Hove, Mortier, Mundhenke, Hermansson, & Natterlund, 2010), and cochlear implants (Preisler, Tvingstedt, & Ahlstrom, 2005). Thus, their perspectives should be investigated and valued, especially on issues that are closely associated with their daily lives.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…Again, here, the perspectives of children who experience disability in relation to these understandings are rarely considered. However, some research that has considered children’s views about and experiences of disability, reveals that adults commonly assume children will have far more negative views about their experiences of impairment than is often the case (Connors and Stalker, 2007; McMaugh, 2011; Serdity and Burgmann, 2012). The aspects of children’s lives and experiences of disability that children find difficult are frequently not those that adults expect (Connors and Stalker, 2007; Serdity and Burgman, 2012).…”
Section: Inclusion Disability and Inclusive Educationmentioning
confidence: 99%
“…However, some research that has considered children’s views about and experiences of disability, reveals that adults commonly assume children will have far more negative views about their experiences of impairment than is often the case (Connors and Stalker, 2007; McMaugh, 2011; Serdity and Burgmann, 2012). The aspects of children’s lives and experiences of disability that children find difficult are frequently not those that adults expect (Connors and Stalker, 2007; Serdity and Burgman, 2012). Importantly, listening to children has been shown to have potential not only to uphold child rights and deepen adult understandings of children’s experiences, but also to enhance educational approaches and experiences and support greater child agency (Nutbrown and Clough, 2009; Paige-Smith and Rix, 2011).…”
Section: Inclusion Disability and Inclusive Educationmentioning
confidence: 99%
“…Specifically, siblings of children with multiple disabilities were found to be more helpful and maternal toward their sibling when compared to their relationships with typically developing siblings [1]. Research has indicated that positive sibling relationships positively impact the development of children and that these relationships foster appropriate identity development [2]. Role-reversal is sometimes found in such sibling relationships, wherein the younger, typically developing sibling assumes the role of the older sibling when interacting with the child that has multiple disabilities [2].…”
Section: Introductionmentioning
confidence: 99%